2015
DOI: 10.1080/19415257.2014.999380
|View full text |Cite
|
Sign up to set email alerts
|

Preschool teachers’ informal online professional development in relation to educational use of tablets in Swedish preschools

Abstract: This paper focuses on preschool teachers' use of online social networks for discussions about tablets in preschools. Posts initiating discussions (n = 465) were analysed to increase understanding of what questions tablets raise among preschool teachers and to understand online communication from a professional development perspective. Posts were analysed using thematic analysis in combination with the Technological Pedagogical Content Knowledge framework, which illustrates what kind of knowledge teachers need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 16 publications
2
14
0
2
Order By: Relevance
“…The use of digital tablets in preschool education in Sweden is on the rise (e.g. Fridberg et al 2017;Marklund 2015;Marklund and Dunkels 2016;Nilsen 2014;Palmér 2015;Petersen 2015). Research results are beginning to provide insight into the influence of different tablet-related activities in preschool pedagogical practice, and on prospective benefits and limitations.…”
Section: Digital Tablets In Swedish Preschool Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of digital tablets in preschool education in Sweden is on the rise (e.g. Fridberg et al 2017;Marklund 2015;Marklund and Dunkels 2016;Nilsen 2014;Palmér 2015;Petersen 2015). Research results are beginning to provide insight into the influence of different tablet-related activities in preschool pedagogical practice, and on prospective benefits and limitations.…”
Section: Digital Tablets In Swedish Preschool Teachingmentioning
confidence: 99%
“…In contrast with documented pedagogical advantages, increasingly identified limitations of integrating tablets has been identified in a study by Marklund (2015) that analysed preschool teachers' online social network discussions around the use of tablets. The work found that teachers often discussed and raised the need for professional development and training in how to integrate tablets in actual pedagogical practice, and into the classroom environment.…”
Section: Digital Tablets In Swedish Preschool Teachingmentioning
confidence: 99%
“…Within the studies reviewed, Ciampa & Gallagher's (2013) seemed to propose the most efficient method for researchers to mentor teachers in implementing mobile media interventions with children in order to ensure the program fidelity of the interventions. An additional element to include for program fidelity would be mentoring early childhood teachers in understanding how technology fits into a developmentally appropriate, play-based program (Marklund, 2015;Nuttall et al, 2015).…”
Section: Teacher Perspectivesmentioning
confidence: 99%
“…For preschool teachers, online learning works best when there is interaction between instructors and other learning peers (Donohue, Fox, & Torrence, 2007). They depend on this form of professional development (Marklund, 2015) and tend to participate more when the online learning content is relevant to their daily work with children (Dede, 2004). It seems likely that online education can provide opportunities for preschool teachers to network with one another without location and time constraints.…”
Section: Preschool Teachers As Online Learnersmentioning
confidence: 99%
“…It is also mentioned that the Internet can offer useful information and learning opportunities, and are increasingly dependent upon this form of professional development (Marklund, 2015). As more preschool teachers enter online education to upgrade their skills or to seek greater educational opportunities, it is important to investigate their online learning experience in order to best design the most appropriate online educational settings for them (Cercone, 2008;Tolliver & Paynter, 2013).…”
Section: Introductionmentioning
confidence: 99%